Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Revisiting Strategies for Bacterial Enumeration: The Case for Viable but Nonculturable (VBNC) Cells in Supplement Products - T. O. Kirby; J. R. Townsend; E. D. Walts; A. Kiefer; J. Zhu; M. Cormier; D. Pathak; C. Wong; A. Castillo; J. Ochoa-Repáraz; R. Jäger; R. H. Lai; et al. (Probiotics and Antimicrobial Proteins, 2026)

Water Use in Rice Crop Cultivation in India: A Quantitative Assessment - Manish Debnath; Sumanta Chatterjee; A. K. Nayak; D. Chakraborty; H. Pathak (Agricultural Research, 2026)

Detection of elevated CO₂ and CH₄ emissions from power plant and landfill sites using airborne and spaceborne imaging spectroscopy - Hasmukh K. Varchand; Mehul R. Pandya; Jalpesh A. Dave; Parthkumar N. Parmar; Dhruv D. Desai; Manoj Singh; Dhiraj B. Shah; Vishal N. Pathak; Himanshu J. Trivedi (Atmospheric Pollution Research, 2025)

Integration of Bioproducts with NPK for Improving Physiological Efficiency of Sugarcane and Sustaining Soil Quality Parameters in Subtropical India - V. P. Jaiswal; S. K. Shukla; Lalan Sharma; A. D. Pathak; Asha Gaur; Abhay Srivastava; Rishi Kumar; Mamta Chaoudhary (Sugar Tech, 2025)

Integration of Mycorrhizae, Azotobacter and Pseudomonas spp (PSB) with NPK and their Effects on Sugarcane Crop and Soil Health in Uttar Pradesh, India - M. K. Tripathi; S. K. Shukla; V. P. Jaiswal; Lalan Sharma; Mona Nagargade; A. D. Pathak; A. P. Dwivedi; Ankur Tripathi; V. K. Singh; V. P. Singh; Ajay Ranka (Sugar Tech, 2025)

Modified emission and scaling factors for methane and nitrous oxide in rice system of India: A country specific disaggregate approach - Pratap Bhattacharyya; A. Bhatia; N. Jain; D. Chatterjee; S. Mohanty; M. Prabhakar; Pratibha M; N.N. Jambhulkar; S. Ananthakrishnan; S.K. Nayak; A.K. Nayak; H. Pathak (Journal of Environmental Management, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

A hybrid physics-based method for estimating land surface temperature using radiative transfer simulations and machine learning model from Sentinel-3A SLSTR observations - Jalpesh A. Dave; Vedant Pandya; Frank-M. Goettsche; Hasmukh K. Varchand; Parthkumar N. Parmar; Dhruv D. Desai; Disha B. Kardani; Dhiraj B. Shah; Ashwin Gujrati; Vishal N. Pathak; Himanshu J. Trivedi; Mehul R. Pandya (Earth Science Informatics, 2025)

Genetic Profiling of Spodoptera litura (Noctuidae: Lepidoptera) in Indian Sub-Tropical Sugar Beet - Santeshwari Srivastava; Varucha Misra; Arun Baitha; Himanshu Pandey; S. N. Sushil; M. Mohan; A. D. Pathak; Sangeeta Srivastava; Dinesh Singh; Ashutosh Kumar Mall (Sugar Tech, 2024)

Phenome-wide genetic-correlation analysis and genetically informed causal inference of amyotrophic lateral sclerosis - Salvatore D’Antona; Gita A. Pathak; Dora Koller; Danilo Porro; Claudia Cava; Renato Polimanti (Human Genetics, 2023)
Leveraging genome-wide association statistics generated from a large study of amyotrophic lateral sclerosis (ALS; 29,612 cases and 122,656 controls) and UK Biobank (UKB; 4,024 phenotypes, up to 361,194 participants), we conducted a phenome-wide analysis of ALS genetic liability and identified 46 genetically correlated traits, such as fluid intelligence score ( r g = − 0.21, p = 1.74 × 10 –6 ), "spending time in pub or social club” ( r g = 0.24, p = 2.77 × 10 –6 ), non-work related walking ( r g = − 0.25, p = 1.95 × 10 –6 ), college education ( r g = − 0.15, p = 7.08 × 10 –5 ), “ever diagnosed with panic attacks ( r g = 0.39, p = 4.24 × 10 –5 ), and “self-reported other gastritis including duodenitis” ( r g = 0.28, p = 1.4 × 10 –3 ). To assess the putative directionality of these genetic correlations, we conducted a latent causal variable analysis, identifying significant genetic causality proportions (gĉp) linking ALS genetic liability to seven traits. While the genetic component of “self-reported other gastritis including duodenitis" showed a causal effect on ALS (gĉp = 0.50, p = 1.26 × 10 –29 ), the genetic liability to ALS is potentially causal for multiple traits, also including an effect on "ever being diagnosed with panic attacks” (gĉp = 0.79, p = 5.011 × 10 –15 ) and inverse effects on “other leisure/social group activities” (gĉp = 0.66, p = 1 × 10 –4 ) and prospective memory result (gĉp = 0.35, p = 0.005). Our subsequent Mendelian randomization analysis indicated that some of these associations may be due to bidirectional effects. In conclusion, this phenome-wide investigation of ALS polygenic architecture highlights the widespread pleiotropy linking this disorder with several health domains.

Enhancing Crop Productivity and Profitability of Autumn Sugarcane with Intercropping of Winter Vegetables in Real Farming Situations of North-Central India - S. N. Singh; Chandra Gupta; V. K. Singh; A. D. Pathak; A. K. Sah; M. K. Tripathi; Sanjiv Gupta; J. R. Patnaik (Sugar Tech, 2023)

Crop Residue Recycling Affecting Carbon Sequestration, Nutrients Availability and Crop Yields in Rice–Wheat and Sugarcane–Ratoon–Wheat System - V. P. Jaiswal; S. K. Shukla; Lalan Sharma; A. D. Pathak (Sugar Tech, 2023)

Adsorption of congo red using carbon from leaves and stem of water hyacinth: equilibrium, kinetics, thermodynamic studies - A. Extross; A. Waknis; C. Tagad; V. V. Gedam; P. D. Pathak (International Journal of Environmental Science and Technology, 2023)

Breeding for Drought Tolerance in Sugarcane: Indian Perspective - A. K. Mall; Varucha Misra; A. D. Pathak; Sangeeta Srivastava (Sugar Tech, 2022)

Plant Quarantine Regulations With Reference to Sugarcane in India: Strengths and Challenges - S. N. Sushil; Deeksha Joshi; Sharmila Roy; G. P. Rao; A. D. Pathak (Sugar Tech, 2022)

Diversification Options in Sugarcane-Based Cropping Systems for Doubling Farmers’ Income in Subtropical India - S. K. Shukla; Lalan Sharma; V. P. Jaiswal; A. P. Dwivedi; S. K. Yadav; A. D. Pathak (Sugar Tech, 2022)

Long-Term Yield of Rice–Rice System with Different Nutrient Management in Eastern India: Effect of Air Temperature Variability in Dry Season - Manish Debnath; Rahul Tripathi; Sumanta Chatterjee; Md. Shahid; B. Lal; Priyanka Gautam; N. N. Jambhulkar; S. Mohanty; D. Chatterjee; B. B. Panda; P. K. Nayak; P. Bhattacharyya; et al. (Agricultural Research, 2022)

Sugar Beet Cultivation in India: Prospects for Bio-Ethanol Production and Value-Added Co-Products - Ashutosh Kumar Mall; Varucha Misra; Santeshwari; A. D. Pathak; Sangeeta Srivastava (Sugar Tech, 2021)

Management of Termites Through Different Tools and Their Impact on Environment and Soil Micro-arthropods in Sugarcane in Indo-Gangetic Plains of India - S. N. Sushil; Sharmila Roy; A. K. Jaiswal; Deeksha Joshi; A. D. Pathak (Sugar Tech, 2021)

Identification of Appropriate Agri-technologies Minimizing Yield Gaps in Different Sugarcane-Growing States of India - S. K. Shukla; Lalan Sharma; V. P. Jaiswal; A. D. Pathak; S. K. Awasthi; Adil Zubair; S. K. Yadav (Sugar Tech, 2021)

Effect of Long-Term Organic Fertilization in Flooded Rice Soil on Phosphorus Transformation and Phosphate Solubilizing Microorganisms - Dibyendu Chatterjee; A. K. Nayak; Annapurna Mishra; C. K. Swain; U. Kumar; D. Bhaduri; P. Panneerselvam; B. Lal; P. Gautam; H. Pathak (Journal of Soil Science and Plant Nutrition, 2021)

Potassium Influencing Physiological Parameters, Photosynthesis and Sugarcane Yield in Subtropical India - V. P. Jaiswal; S. K. Shukla; Lalan Sharma; Ishwar Singh; A. D. Pathak; Mona Nagargade; Arup Ghosh; C. Gupta; Asha Gaur; S. K. Awasthi; Raghvendra Tiwari; Abhay Srivastava; et al. (Sugar Tech, 2021)

Incidence and Diversity of Termites Associated with Sugarcane in North-West Zone of India with New Records - S. N. Sushil; C. M. Kalleshwaraswamy; M. Ranjith; Sharmila Roy; A. K. Jaiswal; Deeksha Joshi; A. D. Pathak (Sugar Tech, 2021)

Sugarcane Yield Using Minimum Tillage Technology Through Subsoiling: Beneficial Impact on Soil Compaction, Carbon Conservation and Activity of Soil Enzymes - S. K. Shukla; V. P. Jaiswal; Lalan Sharma; A. D. Pathak; Akhilesh Kumar Singh; Rajendra Gupta; S. K. Awasthi; Asha Gaur; Adil Zubair; Raghvendra Tiwari (Sugar Tech, 2020)

Determination of Morphological and Biochemical Basis of Resistance Against Top Borer, Scirpophaga excerptalis Walker in Sugarcane - S. N. Sushil; Amaresh Chandra; Sharmila Roy; A. K. Jaiswal; M. R. Singh; A. D. Pathak (Sugar Tech, 2020)

Process of fruit peel waste biorefinery: a case study of citrus waste biorefinery, its environmental impacts and recommendations - Saurabh N. Joglekar; Pranav D. Pathak; Sachin A. Mandavgane; Bhaskar D. Kulkarni (Environmental Science and Pollution Research, 2019)

Green Technologies for Improving Cane Sugar Productivity and Sustaining Soil Fertility in Sugarcane-Based Cropping System - S. K. Shukla; S. Solomon; Lalan Sharma; V. P. Jaiswal; A. D. Pathak; Priyanka Singh (Sugar Tech, 2019)

Ecosystem services in different agro-climatic zones in eastern India: impact of land use and land cover change - Rahul Tripathi; K. C. Moharana; A. D. Nayak; B. Dhal; Md Shahid; B. Mondal; S. D. Mohapatra; P. Bhattacharyya; Nuala Fitton; Pete Smith; A. K. Shukla; H. Pathak; et al. (Environmental Monitoring and Assessment, 2019)

Soil Carbon Sequestration and Crop Yields in Rice–Wheat and Sugarcane–Ratoon–Wheat Cropping Systems Through Crop Residue Management and Inoculation of Trichoderma viride in Subtropical India - S. K. Shukla; Swaha Shee; S. K. Maity; S. Solomon; S. K. Awasthi; Asha Gaur; A. D. Pathak; V. P. Jaiswal (Sugar Tech, 2017)

Crop Diversification Options Involving Pulses and Sugarcane for Improving Crop Productivity, Nutritional Security and Sustainability in India - S. K. Shukla; K. K. Singh; A. D. Pathak; V. P. Jaiswal; S. Solomon (Sugar Tech, 2017)

Habitat Fingerprinting Using Otolith Trace Metal Profile of Two Catfish Species of Genus Ompok (Siluridae) from Ganges Basin, India - U. K. Sarkar; A. K. Pathak; B. K. Gupta; D. D. Patra (Proceedings of the Zoological Society, 2016)

Super-Optimal NPK Along with Foliar Iron Application Influences Bioavailability of Iron and Zinc of Wheat - Rajiv Rakshit; A. K. Patra; T. J. Purakayastha; R. D. Singh; H. Pathak; Shiva Dhar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

Cysteine-rich secretory protein 3 plays a role in prostate cancer cell invasion and affects expression of PSA and ANXA1 - Bhakti R. Pathak; Ananya A. Breed; Snehal Apte; Kshitish Acharya; Smita D. Mahale (Molecular and Cellular Biochemistry, 2016)

Ascorbic acid at pre-anthesis modulate the thermotolerance level of wheat (Triticum aestivum) pollen under heat stress - Ranjeet R. Kumar; Suneha Goswami; Kritika A. Gadpayle; Khushboo Singh; Sushil K. Sharma; G. P. Singh; Himanshu Pathak; Raj D. Rai (Journal of Plant Biochemistry and Biotechnology, 2014)

Sugar Beet: A Historical Perspective in Indian Context - A. D. Pathak; Raman Kapur; S. Solomon; Rajesh Kumar; Sangeeta Srivastava; P. R. Singh (Sugar Tech, 2014)

Differential expression of heat shock protein and alteration in osmolyte accumulation under heat stress in wheat - Ranjeet R. Kumar; Suneha Goswami; Sushil K. Sharma; Khushboo Singh; Kritika A. Gadpayle; S. D. Singh; Himanshu Pathak; Raj D. Rai (Journal of Plant Biochemistry and Biotechnology, 2013)

Dry direct-seeding of rice for mitigating greenhouse gas emission: field experimentation and simulation - H. Pathak; S. Sankhyan; D. S. Dubey; A. Bhatia; N. Jain (Paddy and Water Environment, 2013)

Effect of Zinc Supplementation on the Status of Thyroid Hormones and Na, K, and Ca Levels in Blood Following Ethanol Feeding - R. Pathak; D. Dhawan; A. Pathak (Biological Trace Element Research, 2011)

Maternal and cord blood levels of Aldrin and Dieldrin in Delhi population - MD. Mustafa; Rahul Pathak; A. K. Tripathi; Rafat S. Ahmed; Kiran Guleria; B. D. Banerjee (Environmental Monitoring and Assessment, 2010)

Reproductive pathways of seed development in apomictic guinea grass (Panicum maximum Jacq.) reveal uncoupling of apomixis components - P. Kaushal; D. R. Malaviya; A. K. Roy; Shalini Pathak; A. Agrawal; Ambica Khare; S. A. Siddiqui (Euphytica, 2008)

Endosulfan and Other Organochlorine Pesticide Residues in Maternal and Cord Blood in North Indian Population - Rahul Pathak; Sanvidhan G. Suke; Rafat S. Ahmed; A. K. Tripathi; Kiran Guleria; C. S. Sharma; S. D. Makhijani; Meenu Mishra; B. D. Banerjee (Bulletin of Environmental Contamination and Toxicology, 2008)

Stochastic Modeling of Progressive Failure in Heterogeneous Soil Slope - D. R. Pathak; H. N. Gharti; A. B. Singh; A. Hiratsuka (Geotechnical and Geological Engineering, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Major Indian expeditions ofSaccharum complex - A. D. Pathak; H. M. Srivastava; N. Kulshreshtha (Sugar Tech, 2003)

The role of potassium in sustaining yields in a long-term rice-wheat experiment in the Indo-Gangetic Plains of Nepal - Regmi A.; Ladha J.; Pasuquin E.; Pathak H.; Hobbs P.; Shrestha L.; Gharti D.; Duveiller E. (Biology and Fertility of Soils, 2002)

Mitigation of N 2 O emission from an alluvial soil by application of karanjin - Majumdar D.; Dutta A.; Kumar S.; Pathak H.; Jain M. (Biology and Fertility of Soils, 2001)